Anesthesia Considerations in Infective Endocarditis. (4th February 2022) - Hermanns, Henning; Eberl, Susanne; Terwindt, Lotte E.; Mastenbroek, Thierry C. B.; Bauer, Wolfgang O.; van der Vaart, Thomas W.; Preckel, Benedikt
Abstract : The management of infective endocarditis is complex and inherently requires multidisciplinary cooperation. About half of all patients diagnosed with infective endocarditis will meet the criteria to undergo cardiac surgery, which regularly takes place in urgent or emergency settings. The pathophysiology and clinical presentation of infective endocarditis make it a unique disorder within cardiac surgery that warrants a thorough understanding of specific characteristics in the perioperative period. This includes, among others, echocardiography, coagulation, bleeding management, or treatment of organ dysfunction. In this narrative review article, the authors summarize the current knowledge on infective endocarditis relevant for the clinical anesthesiologist in perioperative management of respective patients. Furthermore, the authors advocate for the anesthesiologist to become a structural member of the endocarditis team. Abstract : Infective endocarditis is a challenging disease, requiring multidisciplinary treatment. In this review article, the authors summarize current knowledge on infective endocarditis that is relevant for the anesthesiologist involved in the treatment of those patients.